Spiritual and Moral Competence and its Importance in Training Future Pedagogues - Tokhtabayevich, Aldashev Ilkhomjon (International Journal of Formal Education, 2024)
The article examines the theoretical and methodological foundations and effectiveness of developing the moral and ethical competence of future pedagogues, the improved methodical foundations and technological system of developing the moral and ethical competence of future pedagogues. Also, spiritual and moral competence and its importance in training future pedagogues was analyzed.